Single-cell transcriptomic analysis identifies a MIF-driven keratinocyte-macrophage-Th2 axis as a key inflammatory circuit in atopic dermatitis - Yan Wei; Rui-Min Bai; Hao-Ran Guo; Jin Shan; Li-Juan Wang; Yan Zhou; Kuan-Hou Mou; Yan Zheng; Ya-Guang Zhang (Inflammation Research, 2026)

ERK1/2 activation in anti-inflammatory effects and underlying signaling mechanisms - Kaiwen Tao; Lin Xu; Chao Cheng; Fukang Yuan; Yicheng Yu; Lidan Zhang; Runmin Li; Rui Xia; Haibei Dong; Xingqi Wang (Inflammation Research, 2026)

Macrophages with ITIH4 overexpression attenuate inflammatory responses and regulate intestinal epithelial cells - Jing Li; Zhuoqi Zhao; Jun Fei; Rui Zhang; Liya Pan; Ying Xiang; Li Hong; Zhiyan Zhan (Inflammation Research, 2026)

PINK1 deacetylation by emodin-induced SIRT3 upregulation alleviates acute kidney injury by Inhibition of ferroptosis - Rui Wang; Ziwei Zou; Yi An; Liulin Wang; Chengyin Li; Yinshui Zou; Guangzhi Wang (Inflammation Research, 2026)

PGC1α alleviates M1 macrophage polarization through dual regulation of succinate metabolism and TRAF5 expression to mitigate TLR4/NF-κB-driven inflammatory cascades and myocardial ischemia/reperfusion injury - Jiajie Leng; Zhenrui Cao; Letai Li; Dingheng Hu; Yuxiang Luo; Bin Tu; Xiaoying Cao; Rui Tao; Yingjiu Jiang; Hongtao Tie (Inflammation Research, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

SARS-CoV-2 nucleocapsid protein induces a Mincle-dependent macrophage inflammatory response in acute kidney injury - Rui-zhi Tan; Wen-jing Zhao; Jing Gao; Hui-yao Lan; Jian Liu; Li Wang (Inflammation Research, 2025)

Rosiglitazone attenuates Acute Kidney Injury from hepatic ischemia–reperfusion in mice by inhibiting arachidonic acid metabolism through the PPAR-γ/NF-κB pathway - Xiaoyan Qin; Zhengli Tan; Qi Li; Shiyi Zhang; Dingheng Hu; Denghui Wang; Liangxu Wang; Baoyong Zhou; Rui Liao; Zhongjun Wu; Yanyao Liu (Inflammation Research, 2024)

Calycosin inhibited MIF-mediated inflammatory chemotaxis of macrophages to ameliorate ischemia reperfusion-induced acute kidney injury - Hong-Lian Wang; Ze Peng; Yu-Qing Li; Yi-Xuan Wang; Jian-Chun Li; Rui-Zhi Tan; Hong-Wei Su; Hong-Ping Shen; Chang-Ying Zhao; Jian Liu; Li Wang (Inflammation Research, 2024)

Salmonella spvC gene suppresses macrophage/neutrophil antibacterial defense mediated by gasdermin D - Liting Zhou; Yuanyuan Li; Jiayi You; Chaoyi Wu; Lingli Zuo; Yilin Chen; Li Kang; Zhengyu Zhou; Rui Huang; Shuyan Wu (Inflammation Research, 2024)

Nafamostat mesilate prevented caerulein-induced pancreatic injury by targeting HDAC6-mediated NLRP3 inflammasome activation - Peng Chen; Li-Jun Zhao; Ling Huang; Wen-Qi He; Ying-Rui Tang; Yi Liu; Jian-Dong Ren (Inflammation Research, 2023)

Featured immune characteristics of COVID-19 and systemic lupus erythematosus revealed by multidimensional integrated analyses - Xingwang Zhao; Mengjie Zhang; Yuying Jia; Wenying Liu; Shifei Li; Cuie Gao; Lian Zhang; Bing Ni; Zhihua Ruan; Rui Dong (Inflammation Research, 2023)

Causal associations of circulating Helicobacter pylori antibodies with stroke and the mediating role of inflammation - Xingzhi Guo; Peng Tang; Xin Zhang; Rui Li (Inflammation Research, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Multi-target regulation of pro-inflammatory cytokine production by transcription factor Blimp-1 - Qiushi Qin; Rui Li; Lan Li; Yue Zhang; Shuwei Deng; Liuluan Zhu (Inflammation Research, 2023)
Objective Cytokine storm syndrome is a fatal condition related to infectious and autoimmune diseases. Here, we aim to investigate the regulatory mechanisms of Blimp-1 on multiple cytokine production. Methods The Blimp1 shRNA was transfected into RAW264.7 macrophages, followed by Toll-like receptor (TLR) ligand stimulation. The mRNA and protein levels of cytokines were detected by real-time PCR and flow cytometric bead array. The nuclear translocation of AP-1 and NF-κB p65 was measured by immunofluorescence staining. The transcriptional activity was detected by luciferase reporter assay with 5 × NF-κB reporter or with IL6 promoter reporter. Results Blimp-1 significantly inhibited the expression and secretion of IL-1β, IL-6, and IL-18 in macrophages during stimulation with a variety of TLR ligands. The immunofluorescence staining results showed that Blimp-1 strictly controlled the nuclear translocation of NF-κB p65 in LPS-challenged macrophages. Furthermore, Blimp-1 directly inhibited the transcriptional activity of NF-κB and the transcription of IL6 gene. Conclusion Blimp-1 represses the production of multiple pro-inflammatory cytokines by directly binding the genomic region and restricting the nuclear translocation and transcriptional activity of NF-κB. This finding may provide potential therapeutic strategies for the cytokine storm-related diseases.

Demethyleneberberine alleviates inflammatory bowel disease in mice through regulating NF-κB signaling and T-helper cell homeostasis - Ying-Ying Chen; Rui-Yan Li; Mei-Jing Shi; Ya-Xing Zhao; Yan Yan; Xin-Xin Xu; Miao Zhang; Xiao-Tong Zhao; Yu-Bin Zhang (Inflammation Research, 2017)

CXCL16 upregulates RANKL expression in rheumatoid arthritis synovial fibroblasts through the JAK2/STAT3 and p38/MAPK signaling pathway - Chang-hong Li; Lin-lin Xu; Jin-xia Zhao; Lin Sun; Zhong-qiang Yao; Xiao-li Deng; Rui Liu; Lin Yang; Rui Xing; Xiang-yuan Liu (Inflammation Research, 2016)

Bencycloquidium bromide inhibits nasal hypersecretion in a rat model of allergic rhinitis - Rui Long; Yuanda Zhou; Jiangju Huang; Li Peng; Long Meng; Shenyin Zhu; Juan Li (Inflammation Research, 2015)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

Postconditioning with vagal stimulation attenuates local and systemic inflammatory responses to myocardial ischemia reperfusion injury in rats - Qiang Wang; Yi Cheng; Fu-Shan Xue; Yu-Jing Yuan; Jun Xiong; Rui-Ping Li; Xu Liao; Jian-Hua Liu (Inflammation Research, 2012)

Combined effects of a neutrophil elastase inhibitor (sivelestat sodium) and a free radical scavenger (edaravone) on lipopolysaccharide-induced acute lung injury in rats - Tao Yang; Junjie Zhang; Lulu Sun; Xiaoyan Zhu; Jinbao Li; Jiafeng Wang; Hui Chen; Rui Bao; Xiaoming Deng; Jiong Hou; Yujian Liu (Inflammation Research, 2012)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

The effect of the expression of angiotensin II on extracellular matrix metalloproteinase inducer (EMMPRIN) in macrophages is mediated via the AT1/COX-2/PGE2 pathway - Li-xia Yang; Jin-shan Ye; Rui-wei Guo; Hong Liu; Xian-mei Wang; Feng Qi; Chuanming Guo (Inflammation Research, 2010)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)